Review Article of Beattie, Peter M. Punishment in Paradise (AmeriQuests, 2017)
Review of Beattie, Peter M. Punishment in Paradise: Race, Slavery, Human Rights, and a Nineteenth-Century Brazilian Penal Colony. Durham: Duke University Press, 2015.